High Density Lipoprotein: Assembly, Structure, Cargo, and Functions. (25th December 2013) - Murphy, Andrew J.
Abstract : Cardiovascular disease (CVD) is the leading cause of death globally. For close to four decades, we have known that high density lipoprotein (HDL) levels are inversely correlated with the risk of CVD. HDL is a complex particle that consists of proteins, phospholipids, and cholesterol and has the ability to carry micro-RNAs. HDL is constantly undergoing remodelling throughout its life-span and carries out many functions. This review summarizes many of the different aspects of HDL from its assembly, the receptors it interacts with, along with the functions it performs and how it can be altered in disease. While HDL is a key cholesterol efflux particle, this review highlights the many other important functions of HDL in the innate immune system and details the potential therapeutic uses of HDL outside of CVD.